Comparison of Transverses Abdominis Plane (Tap) Block with Ilioinguinal and Iliohypogastric Nerve Block As A Part of Multimodal Analgesia During Inguinal Hernia Repair - LEENA AZIZ , UMAR FAROOQ, MUHAMMAD ARSH, TAHIR MAHMOOD CHAUDHRY (Journal of Fatima Jinnah Medical University, 2018)
The objective of the study is to compare the efficacy of two nerve blocks during general anaesthesia in patients undergoing elective inguinal hernia repair. Methods: In this experimental study 120 patient of ASAP1 and P2 status aged 18-60 years of both sex, undergoing elective inguinal hernia repair were selected and divided in two groups of 60 each. The nerve blocks were given after general anaesthesia. Surgery was started after the block and changes in heart rate and blood pressure were noted. At recovery the pain was assessed by VAS scale. Conclusion: Both blocks were found effective in reliving the pain in inguinal hernia repair and no statistically significant difference was noted